Decidualised fallopian tube endometriotic implant causing spontaneous haemoperitoneum in a twin pregnancy. (17th July 2014) - Aggarwal, Ieera; Tan, Pamela; Mathur, Manisha
Abstract : Spontaneous haemoperitoneum in pregnancy (SHiP) is a rare but serious condition associated with an adverse pregnancy outcome. We present a case of previable twin pregnancy presenting with SHiP secondary to endometriosis, necessitating an emergency laparotomy and hysterotomy as a life-saving measure to achieve haemostasis. At laparotomy there was massive haemoperitoneum with active bleeding from the left fallopian tube and a left salpingectomy was performed. Histological examination showed haemorrhagic foci of endometriosis on the fallopian tube exhibiting florid stromal decidual change. We wish to raise awareness of this uncommon but potentially life-threatening condition requiring early recognition and prompt recourse to surgical intervention to minimise the morbidity and mortality.